Perancangan Web Consultant Berbasis Website Full Stack “Bizstarter” - Muhamad Zulio Arrafi; Ahmad Husaein; Herti Yani; Beny Beny; Xaverius Sika (Prosiding Seminar Nasional Ilmu Teknik, 2025)
Many new business owners are seeking easy and simple business consulting services amid rapid technological advances. Unfortunately, most available platforms only offer consulting, not a place to consult and create websites. Biz Starter was created to meet this need, by becoming a platform that not only offers consulting services but also helps users build websites for their own businesses. The development process uses a user-oriented approach, starting from identifying needs, designing the appearance, and then conducting testing. The results show that it is quite helpful for users, especially beginners, because the appearance is simple, the flow is clear, and the business process is much more practical. Overall, this platform has succeeded in making the user experience easier, and it can serve as a digital companion for people who are preparing for business consulting.